Effectiveness of Spiritual Intervention toward Coping and Spiritual Well-being on Patients with Gynecological Cancer - Lina Anisa Nasution; Yati Afiyanti; Wiwit Kurniawati (Elsevier, 2020)
Objective: Coping and spiritual well-being are two important things in improving quality of life of patients with gynecological cancer. However, both of them are still neglected. Spiritual interventions are one of the alternatives in improving coping and spiritual well-being of patients with gynecological cancer. Right now, this intervention is not developed yet in Indonesia, especially about the effect on coping and spiritual well-being. This study aims at determining the effectiveness of spiritual intervention toward coping and spiritual well-being on patients with gynecological cancer. Methods: This was a quantitative research with quasi-experimental method and used a pre- and posttest with control design. The number of respondents in this study was 108 patients (54 patients in each group) and used consecutive sampling. The intervention group received spiritual intervention and the control group received usual care. Spiritual intervention was provided by certified oncology nurses of spiritual training. The instrument used for measuring coping is Brief COPE Scale and Functional Assessment of Chronic Illness Therapy-Spiritual Therapy (FACIT-Sp-12) for measuring spiritual well-being. Results: There was a positive change in the average scores of coping (P = 0.001) and spiritual well-being in the intervention group after receiving spiritual intervention (P = 0.006). The result of this research also shows that there was a significant difference in the average score of coping (P = 0.004) and spiritual well-being (P = 0.001) after spiritual intervention between intervention and control groups. Conclusions: This study shows that coping and spiritual well-being in the intervention group increased significantly after receiving spiritual intervention.